THE IMPACT OF DEMOGRAPHIC CHANGES ON THE PENSION SYSTEM FINANCING SUSTAINABILITY IN THE FEDERATION OF BOSNIA AND HERZEGOVINA - Slavo Vukić; Danijel Knežević (Economic Review)
The aging of the population causes unfavourable demographic trends that are significantly affecting the current state and the future of pension systems on a global basis. The increased number of pensioners and a significant decrease in the rate of demographic reproduction have negative effects on the sustainability of pension systems based on intergenerational solidarity (pay as you go systems), which are prevalent in most European countries. In this paper, the issue of demographic aging and pension systems is analysed from the point of view of sustainability of public finance in the Federation of Bosnia and Herzegovina (FBiH). There are three projected scenarios and the worst one is based on the assumption that pension expenditures will grow at a pace similar to the period from 2002 to 2012. In that case, the share of pension expenditures of Gross Domestic Product (GDP) in 2035 would be over 25%, which is unsustainable by any means. According to long-term projections of the reformed pension system of the FBiH, the greater stability of initial and average pensions, as well as stable social security of pensioners, will result in a relatively stable share of pension expenditures in GDP, of about 10%.